Economic Valuation of Sentul Chicken in the Framework of Providing Incentives and Sustainability of Animal Genetic Resources (AnGR) in Ciamis District, West Java - Rinari Agrian Firdaus; Andre Rivianda Daud; Indrawati Yudha Asmara (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
The purpose of this study was to examine the economic valuation of Sentul chicken to determine the amount of incentive farmers should receive. A survey method has been conducted as the research methodology. The research location was determined purposively, namely in accordance with the research objectives, on the basis of several considerations, the location where the research was located was the Sentul chicken development center where there were active farmer groups. A total of 39 farmers who had a minimum of 100 Sentul chickens/year were censused to become respondents. Data collection was carried out in May - August 2022. The data were analyzed by the contingent valuation method (CVM) using the willingness to accept (WTA) approach in the bidding game. The WTA value sought is the Total WTA (TWTA) and Mean WTA (EWTA) which are converted into incentive values for farmers. Multiple regression analysis has been applied to investigate any significant factors that affected the WTA value. The study results show an estimated total WTA value of IDR 191,220,000 per year and an estimated WTA value of IDR 178,974.36 per chicken per year. Education, experience, land area, income, livestock orientation, and pride are WTA factors that impact farmers, as income (0,024) and pride (0,000) become the most influential factors. Efforts to conserve Sentul chickens can be realized using the incentives indicated by a high WTA value. Therefore, policy makers can conserve Sentul chickens using an incentive approach.